Associations between family suicide and personal suicidal behaviour among youth in KwaZulu-Natal, South Africa - N.B.M. Vawda (South African Family Practice)
Background: For every suicide, a minimum of six people are affected. Given the increasing number of suicide deaths in South Africa, the associations between the suicide of a family member and personal suicidal behaviour were explored in grade 8 students.